2017
DOI: 10.1371/journal.pone.0183799
|View full text |Cite
|
Sign up to set email alerts
|

Top-down influence on gaze patterns in the presence of social features

Abstract: Visual saliency maps reflecting locations that stand out from the background in terms of their low-level physical features have proven to be very useful for empirical research on attentional exploration and reliably predict gaze behavior. In the present study we tested these predictions for socially relevant stimuli occurring in naturalistic scenes using eye tracking. We hypothesized that social features (i.e. human faces or bodies) would be processed preferentially over non-social features (i.e. objects, anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

6
3

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 49 publications
1
39
1
Order By: Relevance
“…Regarding the presence of face/human (Fig. 5), previous research showed that people prioritize their attention to faces, bodies, and other people (i.e., social features) in naturalistic scenes where they could obtain important social information (Bindemann et al, 2010;Cerf et al, 2009;End & Gamer, 2017;Flechsenhar & Gamer, 2017;Scrivner et al, 2019), suggesting scenes with informative and salient scene features, such as faces and people, may produce higher fixation map consistency than scenes without those. For example, Wilming and colleagues (2011) showed that fixation map consistency was higher in urban scenes than in nature scenes and explained that urban scenes have more people and concrete man-made objects, which are more likely to attract fixations.…”
Section: Discussionmentioning
confidence: 98%
“…Regarding the presence of face/human (Fig. 5), previous research showed that people prioritize their attention to faces, bodies, and other people (i.e., social features) in naturalistic scenes where they could obtain important social information (Bindemann et al, 2010;Cerf et al, 2009;End & Gamer, 2017;Flechsenhar & Gamer, 2017;Scrivner et al, 2019), suggesting scenes with informative and salient scene features, such as faces and people, may produce higher fixation map consistency than scenes without those. For example, Wilming and colleagues (2011) showed that fixation map consistency was higher in urban scenes than in nature scenes and explained that urban scenes have more people and concrete man-made objects, which are more likely to attract fixations.…”
Section: Discussionmentioning
confidence: 98%
“…These findings add to pre-existing knowledge on social attention by disentangling the contributions of different face types in naturalistic scenes. Previously, a general strong prioritization of social features (e.g., human heads or bodies) had been described in the literature (Bindemann et al, 2005;Birmingham et al, 2008;Coutrot and Guyader, 2014;End and Gamer, 2017;Flechsenhar and Gamer, 2017;Rösler et al, 2017;Flechsenhar et al, 2018), yet the use of stimulus material varied widely. While many researchers relied on isolated or schematic, artificial faces (e.g., Bindemann et al, 2005Bindemann et al, , 2008Theeuwes and Van der Stigchel, 2006), others employed static or dynamic stimuli representing real humans in naturalistic settings (e.g., Birmingham et al, 2008;End and Gamer, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…When exploring our surroundings, we preferentially allocate attention to other human beings. Various eye-tracking studies have shown that our strong tendency to fixate others is apparent both when viewing images or videos in laboratory settings (Itier et al, 2007;Birmingham and Kingstone, 2009;Cerf et al, 2009;Kingstone, 2009;Bindemann et al, 2010;Coutrot and Guyader, 2014;Xu et al, 2014;Nasiopoulos et al, 2015;End and Gamer, 2017;Flechsenhar and Gamer, 2017;Rösler et al, 2017) and, although to a slightly reduced extent, in real-life social interactions (Foulsham et al, 2011;Laidlaw et al, 2011;Freeth et al, 2013). Among these different viewing modalities, a strong preference for heads (Freeth et al, 2013) and, if stimulus resolution allows, eyes of others (Birmingham et al, 2008) can be discerned.…”
Section: Introductionmentioning
confidence: 99%
“…At the core of interpreting the social dynamics of a scene lies an attentional bias towards the fellow humans taking part in it . Various laboratory studies have shown increased gaze towards human bodies and, in particular, faces, independent of the task at hand (Flechsenhar & Gamer, 2017) or the surrounding visual information (Birmingham, Bischof, & Kingstone, 2009;Boggia & Ristic, 2015;Rösler, End, & Gamer, 2017). However, recent advances in technology have enabled researchers to move the studies on social attention from laboratory settings to the real world.…”
Section: Introductionmentioning
confidence: 99%